Origem e ramificações das artérias faciais em fetos de bovinos azebuados - Núcio, Elisângela Cassimiro Macêdo (2012)
The morphological study, in particular the anatomical, contributes significantly to the applied areas. Hence the importance of studying the facial arteries in fetuses zebul-crossed cattle, which were obtained from slaughterhouses in Uberlândia MG, 20 males and 10 famales. The arterial system received injenção neoprene latex 450 50% (Du Pont do Brazil SA Chemical Industries) via the right common carotid arteries and left. The pieces were fixed in aqueous 10% formaldehyde by subcutaneous injection, intracavitary and intramuscular, as well as his immersion in this solution for a minimum of 48 hours. And subsequently dissected. It was observed that the right facial artery originated from the trunk linguofacial by 90%, and the remaining 10% emerged directly from the external carotid artery and the left originated from the trunk linguofacial in 90% and the remaining 10% emerged from the carotid artery both external and irrigate the digastric, irrigate the digastric, buccinator, depressor upper and lower lip, the zygomatic, nasobabial elevator, lift the upper lip, canine and masseter.